2018
DOI: 10.1111/nmo.13454
|View full text |Cite
|
Sign up to set email alerts
|

Signaling of free fatty acid receptors 2 and 3 differs in colonic mucosa following selective agonism or coagonism by luminal propionate

Abstract: BackgroundPropionate exhibits affinity for free fatty acid receptor 2 (FFA2, formerly GPR43) and FFA3 (GPR41). These two G protein‐coupled receptors (GPCRs) are expressed by enteroendocrine L cells that contain anorectic peptide YY (PYY) and glucagon‐like peptide 1 (GLP‐1), while FFA3 is also expressed by enteric neurons. Few studies have investigated the individual roles of FFA2 and FFA3 in propionate's gastrointestinal (GI) effects. Here, we compared FFA2, FFA3, and propionate mucosal responses utilizing sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 50 publications
1
40
1
Order By: Relevance
“…Indeed, two‐thirds of all patients reported constipation, which was associated with rapid GE2 and slow colon transit. One possible explanation is that rapid GE is associated with exaggerated release of humoral mediators of the ileal brake (ie, GLP‐1, PYY, NPY, leptin, and amylin), which may also delay colonic transit …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, two‐thirds of all patients reported constipation, which was associated with rapid GE2 and slow colon transit. One possible explanation is that rapid GE is associated with exaggerated release of humoral mediators of the ileal brake (ie, GLP‐1, PYY, NPY, leptin, and amylin), which may also delay colonic transit …”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that rapid GE is associated with exaggerated release of humoral mediators of the ileal brake (ie, GLP-1, PYY, NPY, leptin, and amylin), which may also delay colonic transit. 21,[36][37][38][39][40] Only 20% of patients with rapid GE had conditions (ie, autonomic neuropathy or POTS, diabetes mellitus, celiac disease) that have been associated with rapid GE. [5][6][7] Among patients with an autonomic neuropathy or POTS, gastric emptying is more likely to be rapid than delayed.…”
Section: (25)mentioning
confidence: 99%
“…Previous in vivo studies had indicated that administration of SCFAs into the gut (gavage) accelerated gut transit 32 . However, a more recent ex vivo study on isolated colon showed the opposite, where C3, possibly acting via FFA2, decreased gut transit 33 . We resolved this issue using the hFFA2-DREADD-HA mice.…”
Section: An In Vivo Role For Ffa2 In Glp-1 Release and Gut Transitmentioning
confidence: 92%
“…One of the more uncertain aspects of mechanisms behind local effects of SCFA in the gut following their production has been on gut transit time. For example, both (31) and (32) observed SCFAs to reduce gut transit. By contrast Bolognini et al, (19) showed that in wild type C57BL/6 mice provision of C3 in the drinking water resulted in enhanced gut transit.…”
Section: Ffa2 But Not Ffa3 Activation Promotes Gut Transit Timementioning
confidence: 99%